Translating The Term Nafs in The Qur’an Into Indonesian: - fridayanti, Fridayanti; Lu'lu, Dzatul (SUHUF, 2022)
The term nafs has a particular position to be studied due to its complexity in semantics. The study focused on three editions of the Indonesian Al-Qur’an translation published by the Ministry of Religious Affairs of Republik Indonesia: 1990, 2002, and 2019 editions. This study aimed to describe the translations of the term nafs and the possibilities of translation changes in the three editions. This study used a qualitative design with the descriptive-analytical method. The data sources are texts of Al-Qur’an in Arabic and texts of three editions of Al-Qur’an translation in Indonesian. The results show the translations of the term nafs have several themes: first, nafs as desire; second, nafs as a group; third, nafs refers to a person or human; fourth, nafs as structure within a human. In each theme, there are variations of diction. We also found changes and consistencies of dictions used in the three editions of the translation.